2019
DOI: 10.1007/s12110-019-09356-2
|View full text |Cite
|
Sign up to set email alerts
|

Crucial Contributions

Abstract: Maternal grandmothers play a key role in allomaternal care, directly caring for and provisioning their grandchildren as well as helping their daughters with household chores and productive labor. Previous studies have investigated these contributions across a broad time period, from infancy through toddlerhood. Here, we extend and refine the grandmothering literature to investigate the perinatal period as a critical window for grandmaternal contributions. We propose that mother-daughter co-residence during thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 158 publications
(189 reference statements)
2
36
2
Order By: Relevance
“…A growing body of evidence from across non-western, collectivist societies reveals the culturally designated role of these experienced, older women as newborn advisors and caregivers. Unfortunately, at the global level, newborn research, policies and interventions continue to focus primarily on medical technologies and services, 61 to a lesser extent on mothers while giving little attention to intrahousehold newborn strategies in which grandmothers are key components of families' sociocultural operating systems. 4 Research identified from 70 cultural contexts across Africa, Asia and Latin America reveals significant commonalities regarding core roles played by grandmothers with newborns, while their culture-specific BMJ Global Health practices can vary greatly.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence from across non-western, collectivist societies reveals the culturally designated role of these experienced, older women as newborn advisors and caregivers. Unfortunately, at the global level, newborn research, policies and interventions continue to focus primarily on medical technologies and services, 61 to a lesser extent on mothers while giving little attention to intrahousehold newborn strategies in which grandmothers are key components of families' sociocultural operating systems. 4 Research identified from 70 cultural contexts across Africa, Asia and Latin America reveals significant commonalities regarding core roles played by grandmothers with newborns, while their culture-specific BMJ Global Health practices can vary greatly.…”
Section: Discussionmentioning
confidence: 99%
“…Today, Himba are becoming increasingly market-integrated, although communities vary in their distance to town, proximity to the main road and participation in the cash economy [ 50 , 51 ]. Most Himba women continue to give birth in the community, and many return to their natal homes from late pregnancy until 1–6 months after birth in order to obtain help and care from their maternal kin [ 52 , 53 ]. Women’s mothers commonly act as midwives, provide support in learning to breastfeed and oversee postpartum care.…”
Section: Methodsmentioning
confidence: 99%
“…All models included varying intercepts per individual ID, per norm and per village, and population-level effects for age, age-corrected parity and a dummy variable indicating whether or not the participant’s mother was alive. This last variable was included because mothers often act as midwives and are important sources of advice, knowledge and help during the perinatal period [ 52 , 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, the genetic component of this project is just one among many methods and topics the project is focused on. Using ethnographic, demographic and health data we have published studies addressing jealousy (Scelza, 2013b), partner choice , maternal and child health (Prall & Scelza, 2017;Scelza & Hinde, 2019), sleep (Prall, Yetish, Scelza, & Siegel, 2018), marriage and inheritance patterns (Scelza, The project is longitudinal in nature, and concentrates on 40-45 households, with whom we have regular contact. At least one member of the project goes to Namibia each year, along with a team of Namibian research assistants, many of whom have worked multiple field seasons.…”
Section: Introductionmentioning
confidence: 99%
“…However, the genetic component of this project is just one among many methods and topics the project is focused on. Using ethnographic, demographic and health data we have published studies addressing jealousy (Scelza, 2013b), partner choice (Scelza & Prall, 2018), maternal and child health (Prall & Scelza, 2017; Scelza & Hinde, 2019), sleep (Prall, Yetish, Scelza, & Siegel, 2018), marriage and inheritance patterns (Scelza, 2011; Scelza, Prall, & Levine, 2019) and parenting decisions (Scelza et al, 2020a; Scelza & Silk, 2014).…”
Section: Introductionmentioning
confidence: 99%